Human-derived hair follicle stem cells and hydrogen sulfide on focal cerebral ischemia model: A comparative evaluation of radiologic, neurobehavioral and immunohistochemical results - Genç, Çetin; Tahta, Alican; Erdağ, Ece; Dolaş, İlyas; Şahin, Selim; Karaöz, Erdal; Aras, Yavuz; Sabancı, Pulat Akın (Elsevier B.V., 2023)
The present study investigated the effects of intracerebral human-derived hair follicle stem cells (HFBSCs), whether alone or in combination with hydrogen sulfide (H2S) in a rat model of focal cerebral ischemia. The rats were randomly assigned into 4 groups (n = 10): Control (phosphate buffered saline (PBS)), Group A (at 24 h post-middle cerebral artery occlusion(MCAo), stereotaxic intracerebral, 1,0 × 106, total 10 ?L HFBSCs), Group B (3–14 d post-MCAo, intraperitoneal (i.p.), 25 ?M/kg/day H2S), Group AB (HFBSCs + H2S). Cranial magnetic resonance images were recorded on postoperative 1st and 28th days. Three dimensional analysis was performed to calculate the infarct volumes. Rotarod and cylinder tests were performed after MCAo and finally all rats were euthanized by cardiac perfusion at 28 days after MCAo for immunohistochemical analysis. The reduction in infarct volumes of rats receiving HFBSC was significant. The cranial infarct volume on the postoperative 28th day was significantly higher in the group in which H2S was administered alone compared to the HFBSC alone group. All animals showed steadily improved spontaneous locomotor activity from day 7 post-MCAo on rotarod test, from day 1 on cylinder test, but showed no significant differences at all times. In all groups, the grading scores of CD34, CD5, CD11b and GFAP immunohistochemical markers did not differ significantly. In conclusion, intracerebral HFBSC treatment after 24 h of ischemic stroke may be an effective way to reduce the cranial infarct volume, whereas H2S treatment alone or in combination with HFBSC may not be sufficient for ischemic brain injury.
Keywords: Cerebral Ischemia; Hair Follicle Stem Cell; Hydrogen Sulfide; Middle Cerebral Artery Occlusion